2017
DOI: 10.1088/1755-1315/61/1/012083
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and performance evaluation of epoxy-based heat reflective coating for the pavement

Abstract: Abstract. According to the basic characteristics and composition of heat-reflective coating, combining with the functional requirements of road materials, the experiment selects the epoxy resin with good wear resistance and adhesive force as a film forming material, with TiO2, SiO2 and extinction powder as the main functional filler. The experiment gets a good formula with suitable viscosity, low glossiness and good cooling effect, optimizes by orthogonal experiment. The experiment evaluates the indoor and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The temperature difference between each sprayed sample and the control was used as the index to evaluate the cooling effect of the coating. Sunlight exposure was simulated using iodine-tungsten lamps [17,23]; the temperature data were…”
Section: Temperaturementioning
confidence: 99%
See 4 more Smart Citations
“…The temperature difference between each sprayed sample and the control was used as the index to evaluate the cooling effect of the coating. Sunlight exposure was simulated using iodine-tungsten lamps [17,23]; the temperature data were…”
Section: Temperaturementioning
confidence: 99%
“…Outdoor tests and experiments on test sections have also been conducted to further confirm the cooling effect of heat-reflective coatings [7,10,20,21]. Furthermore, Jiang et al reported that heat-reflective pavements have better stability at high temperatures [17,22,23]. This excellent cooling effect is one of the main reasons for the rapid development of heat-reflective coatings for asphalt pavements; in addition, the convenient construction and low cost of heat-reflective coating [5] have made them one of the best solutions to rutting damage and heat island effect caused by asphalt pavements in summer [4,17,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations